Dynamics of change in East Asia historical trajectories and contemporary development - Preston, P. W. (Routledge, Taylor & Francis Group, 2018)
Over the past forty years, East Asia has been radically transformed from a war-damaged sub-continent to a region of global pre-eminence. This book illuminates the historical development trajectory and contemporary circumstances of the countries of the region. Embracing a cross-disciplinary perspective, it summarizes the history of the region and goes on to focus upon the rise of East Asia since the ruins of the Pacific War.